Marketing in religious festivals: The case of Niñopa in Xochimilco, Mexico (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2019)
In order to understand the marketing significance of religious festivities in the economic contribution to a locality's residents, as well as their social and cultural impact, a qualitative, ethnographic, and descriptive study was conducted on the celebration of the Niñopa festival in Xochimilco, a municipality of Mexico City, Mexico. This celebration is the most important in the locality and a significant part of Mexican culture and tradition. The study revealed that marketing is empirically present in every action carried out during this important religious festival, making it a tourist attraction that generates a significant source of economic resources for the area.